La 5e colonne allemande en Pologne - Lesniewski, Andrzej (Warszawa : Wydawnictwo Zachodnie, 1960)
Bibliotheek Camille Huysmans
Frans
Monografie
Keywords: Wereldoorlog 2; Verdrag van Versailles; territoriale kwesties; Polen